Effect of urinary stone disease and extracorporeal shockwave lithotripsy on excretion of glycosaminoglycans - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1999)
Background and Purpose: The effect of glycosaminoglycans (GAGs) in urinary crystal inhibition has been shown in vitro, but their inhibitor role in vivo has not been precisely determined in stone-forming patients. The aim of this study was to compare the levels of total GAGs and their components in primary stone-forming patients and a healthy control group and to investigate the impact of shockwave lithotripsy (SWL). Patients and Methods: Thirty-eight patients with primary kidney stones and 31 healthy controls were included in this prospective study. Total urinary GAG concentrations were determined by the dimethylene blue assay (DMB), and GAG fractions (chondroitin sulfate, heparan sulfate, and dermatan sulfate) were studied by cellulose acetate electrophoresis, Analysis was repeated after SWL in the stone patients. Results: Chondroitin sulfate was the major component secreted in the urine of the control subjects. Heparan sulfate was the major component in the urine of the stone patients with less chondroitin sulfate and dermatan sulfate (48%, 35%, 16.5%, respectively). Our study showed a significant increase in total urinary GAGs (4.75 v 7.43 mu g/mg of creatinine; P < 0.0001) after SWL, Dermatan sulfate was the main component in this group (P < 0.0001). The total urinary GAG concentrations remained high for at least 2 days after SWL. Conclusion: The elevation in total GAGs after SWL indicates the presence of tissue injury, which also renders dermatan sulfate the principal excreted component, Studies with longer follow-up periods are needed to determine whether these changes in the excretion of GAG components persist.
Keywords: CALCIUM-OXALATE; WAVE LITHOTRIPSY; FORMING SUBJECTS; URIC-ACID; AGGREGATION; INHIBITORS; FORMERS